NIGELLA SATIVA OIL AS AN ADD-ON IN THE CONSERVATIVE MANAGEMENT OF DIABETIC NEPHROPATHY: A NOVEL SYNERGISTIC APPROACH - MOHD ASHRAF ALAM; MOHAMMAD NASIRUDDIN; SHAHZAD F HAQUE; RAHAT A KHAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to evaluate efficacy and safety Nigella sativa oil as an add-on therapy in addition to alpha-keto analog of essential amino acids in patients diabetic nephropathy (DN). Methods: The study was conducted in a tertiary care center of North India on patients of DN. It was a prospective, comparative, and open labeled study. Patients were randomly divided into two interventional groups. Group I (control) received conservative management of chronic kidney disease consisting of alpha-keto analog (600 mg tab. 3 times a day), while Group II (test) received conservative management along with alpha-keto analog and N. sativa oil (2.5 ml, per orally, once daily) for 12 weeks. Hemogram and renal function, serum electrolytes tests were done, and adverse events were recorded at baseline, 4, 8, and 12 weeks of treatment. Results: After 12 weeks of treatment, there was a marked improvement in clinical features and biochemical parameters in both the control and test groups, but it was more statistically significant in the test group as compared to control group especially in renal function (p≤0.05). Both groups showed steady improvement in the biochemical parameters as compared to their pre-treated values which were more marked in N. sativa oil supplemented group. There was a reduction in blood glucose, blood urea, serum creatinine, and 24-h total urine protein, and an increase in hemoglobin, 24-h total urine volume, and glomerular filtration rate. Conclusion: N. sativa oil supplementation along with alpha-keto analog is more efficacious and safer in delaying the progression of disease patients of DN.